ANALYSIS OF PHONOLOGICAL LEVEL LANGUAGE ERRORS IN CNN INDONESIA ONLINE NEWS - Chica Chaswati; Dwi Sartika; Dinda Nurdiana; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
This research aims to describe language errors at the phonological level made in CNN Indonesia's online news writing. This research uses a qualitative descriptive method with note-taking data collection techniques. Based on the research results, several language errors were found at the phonological level in the form of seven errors in the use of standard words and five errors in the use of punctuation marks. It can be concluded that the mistakes made were caused by several factors, including not paying attention to linguistic rules and the influence of the relaxed use of everyday language used by news writers.